Contrasting response of native and non‐native plants to disturbance and herbivory in mountain environments. (25th March 2021) - Geppert, Costanza; Boscutti, Francesco; La Bella, Greta; De Marchi, Vittoria; Corcos, Daria; Filippi, Antonio; Marini, Lorenzo
Abstract: Aim: Climate warming and increasing human disturbance are expected to promote non‐native plant invasions in mountain ecosystems. Although biological invasions are also expected to be modulated by biotic interactions, it is still not clear how invertebrate herbivores can affect plant invasion dynamics. Using a large manipulative experiment, we aimed at testing: (1) the effect of soil disturbance and elevation on native and non‐native plant communities, and (2) the effect of plant‐herbivore interactions, nitrogen deposition, and elevation in driving plant establishment after soil disturbance. Location: European Alps, NE Italy. Taxon: Vascular plants. Methods: We selected remote, uninvaded dry semi‐natural grasslands along the core elevational range of non‐native plants in the European Alps (c. 100–1300 m) and manipulated soil disturbance, nitrogen deposition, and invertebrate herbivory. Then, we followed the natural establishment under real field conditions of both native and non‐native plants over one growing season. We used generalized mixed‐effects models to test the effects of the experimental treatments. Results: Native and non‐native species showed contrasting responses to soil disturbance and elevation. Low elevations and disturbance promoted non‐native success, while affecting native species diversity negatively. Two‐thirds of the experimental sites acquired novel non‐natives after disturbance. Most of the observed non‐natives were not present in the surrounding vegetation as mature plants, indicating that propagules were able to reach even remote natural areas. While current N deposition levels did not affect plant establishment, we found that after disturbance invertebrate herbivory might play an important role in facilitating non‐native invasions by reducing native cover. Main conclusions: Our findings show that highly resistant ecosystems such as continuous grasslands can be easily invaded once the resident vegetation has been removed, and that natural herbivory pressure from invertebrates might amplify the negative effects of disturbance on resident native species irrespective of elevation. Together, these results indicate increasing risks of future plant invasions on mountains under global change.